Brief handbook on Spanish Labour Law - Álvarez-Cortés, Juan Carlos; Aragüez-Valenzuela, Lucía Dolores; Baquero Aguilar, Jorge; Macías-García, María del Carmen; Martín-Rivera, Lucía; Martínez-Mateo, Carlos José; McKenzie, Shelagh; Menoya Zayas, Sandys; Mora-Pena, Carmen María; Ordóñez-Casado, María Iluminada; Poyatos Chacón, Fátima; Ramírez Bandera, Cristina; et al. (Laborum, 2024)
Este manual es un recurso útil para estudiantes del derecho laboral que buscan comprender la estructura básica y las aplicaciones prácticas de la legislación laboral española tanto en la vertiente individual como colectiva. Contiene información detallada sobre las instituciones básicas del derecho laboral español y proporciona referencias a la legislación básica de aplicación. This handbook is a valuable resource for labor law students seeking to understand the basic structure and practical applications of Spanish labor legislation, both in individual and collective aspects. It contains detailed information on the fundamental institutions of Spanish labor law and provides references to the key applicable legislation.
Keywords: Derecho laboral - España; Labor Law; Individual Labor Law; Colective Labour Law; Employment contract; Working conditions; Collective bargaining